2020
DOI: 10.1007/s11033-020-05736-5
|View full text |Cite
|
Sign up to set email alerts
|

Identification of proteins involved in transcription/translation (eEF 1A1) as an inhibitor of Bax induced apoptosis

Abstract: Eukaryotic elongation factor 1A1 (eEF1A1) is central to translational activity. It is involved in complexes that form signal transduction with protein kinase C, as well as being a signal transducer and activator of transcription 3. eEF1A1 and eEF1A2 are isoforms of the alpha subunit of elongating factor 1 complex. It has been reported that eEF1A1 is expressed in most human tissues but the brain, skeletal muscle and heart. eEF1A1 has been linked to both apoptosis and anti-apoptotic activities. In this study, eE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 35 publications
(62 reference statements)
0
5
0
Order By: Relevance
“…However, eEF1A2 is expressed in a tissue-specific manner, and eEF1A is expressed ubiquitously ( Li et al, 2019 ). In addition to its roles in polypeptide chain elongation, the noncanonical functions of eEF1A1 have become a focus recently, such as apoptosis ( Akintade and Chaudhuri, 2020 ), virus infection ( White et al, 2021 ), signal transduction ( Akintade and Chaudhuri, 2020 ), and tumorigenesis ( Liu S. et al, 2019 ). Our previous study indicated that MLIF decreased the ICAM-1 and VCAM-1 expression and increased the eNOS expression in OGD- or ox-LDL–induced bEnd3 cells by targeting eEF1A1 ( Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, eEF1A2 is expressed in a tissue-specific manner, and eEF1A is expressed ubiquitously ( Li et al, 2019 ). In addition to its roles in polypeptide chain elongation, the noncanonical functions of eEF1A1 have become a focus recently, such as apoptosis ( Akintade and Chaudhuri, 2020 ), virus infection ( White et al, 2021 ), signal transduction ( Akintade and Chaudhuri, 2020 ), and tumorigenesis ( Liu S. et al, 2019 ). Our previous study indicated that MLIF decreased the ICAM-1 and VCAM-1 expression and increased the eNOS expression in OGD- or ox-LDL–induced bEnd3 cells by targeting eEF1A1 ( Zhang et al, 2012 ).…”
Section: Discussionmentioning
confidence: 99%
“…The role of EEF1A1 in apoptosis has been controversial. EEF1A1 seems to promote apoptosis, while a previous study showed that EEF1A1 only exhibits antiapoptotic effects when the proapoptotic protein Bax is present [21]. Our prior research revealed that cell apoptosis is an important contributor to the onset and progression of myopia.…”
Section: Discussionmentioning
confidence: 74%
“…In mammals, EEF1A is divided into EEF1A1 and EEF1A2 [6]. Studies have reported that EEF1A1 is involved in apoptosis [7], viral infection [8],…”
Section: Introductionmentioning
confidence: 99%
“…signal transduction [7], and tumorigenesis [9]. Liu et al [10] found that down-regulation of EEF1A1 inhibited OGD-induced activation of the JNK pathway and thus inhibited apoptosis, which had a protective effect similar to that of HSC70 in cerebral ischemic injury.…”
Section: Introductionmentioning
confidence: 99%